The Level Of Total Quality Management Practice In Educational Colleges At The University Of Mosul - Ali Abbas, Muhammad; Ghanem Abd, Israa (Opción, 2019)
The research aimed to identify the level of total quality management practice in educational colleges at the University of Mosul from the point of view of male and female teachers and whether there were statistically significant vio- lations in the level of total quality management practice depending on gender variations, specialization, educational qualification or duration of service. The research sample consisted of (232) teaching and teaching students, and a tool consisting of (34) items was constructed after extracting validity and consist- ency. By using the statistical methods represented by the Pearson correlation coefficient, the T-test, and the analysis of variance, the results showed that the level of quality management practice is above the mean, as well as the absence of statistically significant differences in the level of total quality management practice from the teaching point of view due to the gender variable, special- ization, educational qualification and duration of service and a number was developed From directions and suggestions.